All the Public Services by a Single Point in Electronic Government: Government Portal in Iraq - H. safi Al-jebory, Hayder; Abraheim Al-saadi, Husam (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
E-government reflects the ultimate visions for public administration to undergo a huge modernization and re-organization .the project that aims at developing an integrated platform for realizing online one-stop Government ,a global access point to enter different governmental services and information at distinct levels of public administration and with different devices ,the development of one-stop government process models implemented in local service repositories and a governmental markup language as an open standard for data exchange and communication within the platform .